Challenges faced by community- oriented policing trainees In Nigeria (2013)
Community oriented policing training prepares the police trainees on how to partner with the public in crime prevention and control in Nigeria. The trainees after leaving the training grounds still find it difficult to integrate with their colleagues and members of the public in crime prevention and control in Nigeria. The crisis of theory and practice of community oriented policing in Nigeria emerges as the trainees are confronted with both organizational and environmental obstacles in the field. The training of community oriented policing officers need not be in isolation of the operational environment after training. This study unveiled some of the challenges and difficulties experienced by community oriented policing trainees after the training in Nigeria. The study utilized both qualitative and quantitative methods of data collection and analysis. The Gap theory of George J. Thompson was adopted to understand the effects of police interactions with the public after training in community oriented policing in Nigeria.The study revealed some of the challenges faced by police trainees after community oriented policing training in Nigeria and recommended adequate posting and monitoring of the police after training.